Pengaruh Harga dan Kelengkapan Produk terhadap Keputusan Pembelian Toserba Griya Majalengka Kabupaten Majalengka - Eli Dahlia (Ebisnis Manajemen, 2024)
This research aimed to determine whether the price and product completeness influence purchasing decisions, either partially or simultaneously. The population in this research was an unknown number of customers of the Griya Majalengka Department Store. The sample size was calculated using the Cochran formula and the sample in this research is 384 Griya Majalengka Department Store customers was obtained. The method used in this research was verification analysis. The data analysis technique in this research used multiple linear regression analysis. Based on the results of hypothesis testing, this research had 3 findings. First, price had a positive effect on purchasing decisions. Second, product completeness had a positive effect on purchasing decisions. Third, price and product completeness had a positive effect on purchasing decisions simultaneously.